Association of academic stress & performance in continuous assessment among pharmacy students in body system course - May, Khin Soe; Baharudin, Mohamad Sharul Fahmi (2016)
Undergraduate Pharmacy students find the program is stressful. This study compares the perceived stress score (PSS) of third year Pharmacy students and their performance via continuous assessment (CAM) in Body System course. The relationship between the PSS and their academic performance throughout the semester were explored for 114 students including 25 male and 85 female. In this cross-sectional study, questionnaires were distributed to assess their PSS, other relevant questions and the result in four quizzes of the course were recorded periodically and analysed descriptively. The mean value of the whole class PSS score was found (38.66 ± 6.46). Females’ PSS in 1st quiz was 38.76±5.56 and male’s was 39.21±5.48 and quiz 2 for female was 38.61±6.27 whereas 40.1± 7.48 in male. That value in quiz 3 and 4 for female was 38.10±7.18 and male was 39.69±8.68. However, there is no significant difference in gender. The PSS score for all participants was found highest in the second quiz (38.99 ± 6.60) whereas the mean marks they obtained were lowest (4.97±1.36) compared to other quizzes but their relation is weakly significant. Total scoring of the CAM for the whole class was found even lower compared to previous batches, 23.83 ±3.88. They were engaged with various co-curriculum activities and complained of not having enough time to study and revise. The unsatisfactory performance might be due to heavy topics and time constraint. Stress and time management are critical elements for undergraduate students to perform well academically regardless of their stress level.